PENGELOLAAN SAMPAH BERBASIS MASYARAKAT MELALUI PROGRAM BANK SAMPAH DI PEKANBARU - Endah Julita; Zukarnaini Zukarnaini; Sofyan Husein Siregar (Program Pascasarjana Universitas Riau, 2018)
community needs and demands, planned, implemented (if feasible), controlled and evaluated with the community. One of the alternatives that has been proposed to solve the problem of waste in various regions in Indonesia is the garbage bank. The construction of garbage bank is the initial momentum to build collective consciousness of the community to start sorting, recycling, and utilizing garbage because garbage has good selling value, so that environmentally sound waste management becomes new culture of Indonesia. This study aims to analyze community-based waste management through waste bank programs in Pekanbaru and analyze the relationship of waste bank management to environmental, economic and social impacts. The research was conducted at garbage bank of Dalang Collection and BerlianLabuai with 142 respondents. Data collection was done by observation, interview, and questionnaire. Data analysis techniques using descriptive analysis techniques and product moment correlation. From the result of research, the correlation between variable X (waste bank management) and Y (environmental, economic and social impact) is 0,660, and contribution of waste bank management to environmental, economic and social impact is 43,56%. Based on the result of t test analysis obtained tcount (10,39)>ttabel (1,645). Thus it can be concluded that there is a significant relationship between waste bank management on environmental, economic and social impacts.